Long-Term Endurance Exercise Training Alters Repolarization in a New Rabbit Athlete’s Heart Model - Kui, Péter; Polyák, Alexandra; Morvay, Nikolett; Tiszlavicz, László; Nagy, Norbert; Ördög, Balázs; Takács, Hedvig; Leprán, István; Farkas, András; Papp, Julius Gy.; Jost, Norbert; Varró, András; et al. (Frontiers in Physiology, 2022)
In the present study, the effect of long-term exercise training was investigated on myocardial morphological and functional remodeling and on proarrhythmic sensitivity in a rabbit athlete's heart model. New-Zealand white rabbits were trained during a 12-week long treadmill running protocol and compared to their sedentary controls. At the end of the training protocol, echocardiography, in vivo and in vitro ECG recordings, proarrhythmic sensitivity with dofetilide 50 nM were performed in isolated hearts and action potential duration (APD) measurements at different potassium concentrations (4 and 2 mM) were made in isolated papillary muscles. Expression levels of the slow component of delayed rectifier potassium current and fibrosis synthesis and degradation biomarkers were quantified. Echocardiography showed significantly dilated left ventricle in the running rabbits. ECG PQ and RR intervals were significantly longer in the exercised group (79±2 ms vs. 69±2 ms and 325±11 ms vs. 265±6 ms, p<0.05, respectively). The in vivo heart rate variability (Standard Deviation of Root Mean Square: 5.2±1.4 ms vs 1.4±0.2 ms, p<0.05) and Tpeak-Tend variability was higher in the running rabbits. Bradycardia disappeared in the exercised group in vitro. Dofetilide tended to increase the QTc interval in a greater extent, and significantly increased the number of arrhythmic beats in the trained animals in vitro. APD was longer in exercised group at low potassium level. RT-qPCR showed significantly greater messenger RNA expression of fibrotic biomarkers in the exercised group. Increased repolarization variability and higher arrhythmia incidences, lengthened APD at low potassium level, elevated fibrotic biomarker gene expressions may indicate higher sensitivity of the rabbit "athlete's heart" to life-threatening arrhythmias.